(untitled) (Annals of Medical Research, 2021)
Aim: To evaluate the outcomes of management of ureteropelvic junction obstruction in premature patients by comparing them to a group of non-premature. Material and Methods: We reviewed the medical records of 102 patients with isolated hydronephrosis which were referred from pediatric nephrology outpatient clinic or those who admitted directly to pediatric urology clinic under one year of age between the years of 2005 and 2016. Two groups were set up; premature and term. The gestational age, sex, management for ureteropelvic junction obstruction, complications were recorded. Chi-Square, Fisher’s and Mann-Whitney-U tests were used for statistical analyzes. Results: There were 92 patients in the term group and 10 in the premature group. All patients were operated. Preoperative symptoms such as pyonephrosis, renal calculi, and hypertension were relatively common in the premature group. Preoperative low function, postoperative loss of function, and poor outcome were statistically more common in premature patients. Conclusion: In our limited experience, prematurity is an independent factor associated with UPJO, and it may indicate a poor prognosis. We advocate that this issue should be considered in practice.